Landraces of durum wheat (Triticum durum Desf.) in the VIR collection - O. A. Lyapunova (Труды по прикладной ботанике, генетике и селекции)
The collection of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) harbors 3,633 accessions of durum wheat landraces from 49 countries. This is a unique heritage, currently neither cultivated in the places of its origin nor found in any collection over the world. This review explores the history of the collection of landraces, its structure, and diversity of the preserved genotypes. Descriptions of landraces from different countries and examples of their successful utilization in breeding practice are presented. Special attention is paid to the collection of Russian landraces. Today, the problem of utilizing obsolete local cultivars is relevant in the context of the shrinking diversity of modern cultivars and genetic erosion of the source material for breeding. Innovative methods based on the use of molecular markers demonstrate new trends in the study and utilization of landraces in different regions.